Perlindungan Hukum bagi Konsumen Shopee Paylater dalam Menghadapi Wanprestasi - Ni Nyoman Trisna Pradewi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The development of the internet in Indonesia has opened up numerous opportunities, including in the field of online commerce. One widely used feature in online transactions is the